Prospective meta-analysis protocol on randomised trials of renin–angiotensin system inhibitors in patients with COVID-19: an initiative of the International Society of Hypertension - Anthony Rodgers; George Stergiou; Bryan Williams; Sonali Rukshana Gnanenthiran; Markus P Schlaich; Claudio Borghi; Dylan Burger; Fadi Charchar; Neil R Poulter; Ulrike Muscha Steckelings; Maciej Tomaszewski; Thomas Unger; et al. (BMJ Open)
Introduction Whether ACE inhibitors (ACEi) or angiotensin II receptor blocker (ARB) therapy should be continued, initiated or ceased in patients with COVID-19 is uncertain. Given the widespread use of ACEi/ARBs worldwide, guidance on the use of these drugs is urgently needed. This prospective meta-analysis aims to pool data from randomised controlled trials (RCTs) to assess the safety and efficacy of ACEi/ARB therapy in adults infected with SARS-CoV-2.Methods and analysis RCTs will be eligible if they compare patients with COVID-19 randomised to ACEi/ARB continuation or commencement versuss no ACEi/ARB therapy; study duration ≥14 days; recruitment completed between March 2020 and May 2021. The primary outcome will be all-cause mortality at ≤30 days. Secondary outcomes will include mechanical ventilation, admission to intensive care or cardiovascular events at short-term follow-up (≤30 days) and all-cause mortality at longer-term follow-up (>1 month). Prespecified subgroup analyses will assess the effect of sex; age; comorbidities; smoking status; ethnicity; country of origin on all-cause mortality. A search of ClinicalTrials.gov has been performed, which will be followed by a formal search of trial registers, preprint servers, MEDLINE, EMBASE and Cochrane Central Register of Controlled Trials to identify RCTs that meet inclusion criteria. To date, a search of ClinicalTrials.gov identified 21 potentially eligible trials for this meta-analysis. We will request trial investigators/sponsors to contribute standardised grouped tabular outcome data.Ethics and dissemination Ethics approval and informed consent will be the responsibility of the individual RCTs. Dissemination of results will occur by peer-reviewed publication. The results of our analysis can inform public health policy and clinical decision making regarding ACEi/ARB use in patients with COVID-19 on a global scale.